2013
DOI: 10.1016/j.marpol.2012.02.016
|View full text |Cite
|
Sign up to set email alerts
|

Management objectives of Queensland fisheries: Putting the horse before the cart

Abstract: a b s t r a c tA review of future management arrangements for the Queensland East Coast Trawl fishery was undertaken in 2010 to develop a management plan for the next 10 years. A key question raised at the start of the review process was: what should the management plan achieve? As with fisheries management in most countries, multiple management objectives were implicit in policy statements, but were poorly specified in some areas (particularly social objectives) and strongly identified in others (e.g., an obj… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
24
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 53 publications
(24 citation statements)
references
References 25 publications
0
24
0
Order By: Relevance
“…Similarly, perceptions of equitable resource allocation and fishers' trust in management were also not significant in determining satisfaction or desire to leave. This result is perhaps less surprising, as studies of management objective importance in the fishery have found that improving equity has a relatively low importance to fishers compared to improving economic performance (Pascoe et al 2013a). …”
Section: Discussionmentioning
confidence: 99%
“…Similarly, perceptions of equitable resource allocation and fishers' trust in management were also not significant in determining satisfaction or desire to leave. This result is perhaps less surprising, as studies of management objective importance in the fishery have found that improving equity has a relatively low importance to fishers compared to improving economic performance (Pascoe et al 2013a). …”
Section: Discussionmentioning
confidence: 99%
“…Other studies comparing social objectives to economic and environmental objectives have generally found that social objectives overall obtain a relatively low priority (e.g. Pascoe et al, 2013a;Wattage and Mardle, 2005). When presented with a set of specific objectives for the survey, they did not have the advantage of previous discussions by which they could consolidate their views on priorities for social objectives.…”
Section: Discussionmentioning
confidence: 90%
“…fishers, conservation groups and community groups) were not included in the survey as the aim was to assess managers' perceptions of the relative importance of the alternative objectives. Potentially, other stakeholders could be included in the analysis as has been done in other studies (Innes and Pascoe, 2010;Pascoe et al, 2013a). Who to include in the study was discussed at the stakeholder workshop, where the decision to limit it to managers e at least in the first instance e was made on the basis that they were responsible for implementing and achieving these objectives on behalf of the broader community.…”
Section: Ahp Surveymentioning
confidence: 99%
See 1 more Smart Citation
“…The MEY ranged between 1300 t and 2000 t and E MEY between 7000 and 13 000 boat-days. A higher value of d significantly increased profit, but reduced the number of vessels, which may negatively impact social objectives of the fishery Pascoe et al, 2013). Operationalizing MEY in a fishery requires an agreed set of rules, assumptions and strong industry commitment .…”
Section: Reference Pointsmentioning
confidence: 99%